Implementasi Pembelajaran di Era Revolusi Industri 4.0 di SMP Negeri 2 Lubuklinggau - Handayani, Fitri; Arikarani, Yesi; Mukmin, Taufik; Akip, Muhamad (El-Ghiroh : Jurnal Studi Keislaman, 2021)
The development of education is undergoing a rapid, dynamic transformation with technological advances in the era of the industrial revolution 4.0. This change is felt by the teaching and learning process at SMP Negeri 2 Lubuklinggau implementing 4.0-based learning in its application that has not been maximized and the existing technology is not used as well as possible. This study uses a qualitative approach with this type of research being field research, interview data collection techniques, observation and documentation. Analysis technique according to Miles and Humbersman. The findings of the first research, the implementation of PAI learning at SMP Negeri 2 Lubuklinggau still uses conventional methods, complete learning resources, delivering appropriate and clear material. Second, the efforts of teachers in the era of the industrial revolution 4.0 to master learning technology by using smartphones for online learning. Third, the supporters are facilities and infrastructure, internet network, focus, and learning resources. The obstacle is that students feel pampered by technology that is instant and easy to access, students are lazy to read in detail.